Effectiveness of the Apparent Diffusion Coefficient for Predicting the Response to Chemoradiation Therapy in Locally Advanced Rectal Cancer: A Systematic Review and Meta-analysis. Issue 6 (February 2015) - Xie, Haiting; Sun, Tao; Chen, Ming; Wang, Hao; Zhou, Xin; Zhang, Yunkai; Zeng, Huanhong; Wang, Jilian; Fu, Wei
Abstract : Abstract: The efficacy of the different apparent diffusion coefficients (ADCs) in predicting different responses to preoperative chemoradiation therapy (CRT) in patients with locally advanced rectal cancer (LARC) is controversial. We did this meta-analysis to evaluate the efficacy of different ADCs predicting different responses to CRT in patients with LARC. We systematically searched the MEDLINE, Embase, and Cochrane Library databases for articles published from January 1, 1990, to June 3, 2014. Pooled estimates were calculated using a bivariate random-effects model for the ADCs before and after CRT (pre- and post-ADC), as well as the change between the pre- and post-ADC (ΔADC). The values of the 3 ADCs for judging different response endpoints, which were defined according to the tumor grading (TRG) system and downstaging of T (tumor) or N (nodal) stages (TN downstaging), were assessed. We included 16 studies with a total of 826 patients. The sensitivity, specificity, DOR, and AUC were 75% (95% CI 57%–87%), 70% (95% CI 50%–84%), 6.81 (95% CI 2.46–18.88), and 0.79 (95% CI 0.75–0.82), respectively, for the pre-ADC in predicting a good response; 76% (95% CI 63%–85%), 87% (95% CI 78%–92%), 20.68 (95% CI 11.76–36.39), and 0.89 (95% CI 0.86–0.91), respectively, for the post-ADC; and 78% (95% CI 65%–87%), 77% (95% CI 62%–87%), 11.82 (95% CI 4.65–30.04), and 0.84 (95% CI 0.81–0.87), respectively, for the ΔADC. The post-ADC demonstrated the highest specificity and DOR ( P < 0.001), although sensitivity did not differ between the 3 types of ADC ( P = 0.380, 0.192, and 0.214). For predicting a pathological complete response (pCR), the post-ADC had the highest specificity ( P < 0.001and 0.030) but lowest sensitivity ( P < 0.001). The ΔADC had the highest DOR; however, this difference was not statistically significant ( P = 0.146). The ADC is a reliable and reproducible measure and could serve as a promising noninvasive tool for evaluating the response to CRT in patients with LARC; the post-ADC and ΔADC are particularly promising. The ΔADC had the highest diagnostic performance to predict a pCR compared with the pre-ADC and post-ADC. The value of the ADCs to predict T or N downstaging requires further investigation. Abstract : Supplemental Digital Content is available in the text